Hypertensive heart disease: risk factors, complications and mechanisms - Masenga, Sepiso K.; Kirabo, Annet (Frontiers in Cardiovascular Medicine, 2023)
Hypertensive heart disease constitutes functional and structural dysfunction and pathogenesis occurring primarily in the left ventricle, the left atrium and the coronary arteries due to chronic uncontrolled hypertension. Hypertensive heart disease is underreported and the mechanisms underlying its correlates and complications are not well elaborated. In this review, we summarize the current understanding of hypertensive heart disease, we discuss in detail the mechanisms associated with development and complications of hypertensive heart disease especially left ventricular hypertrophy, atrial fibrillation, heart failure and coronary artery disease. We also briefly highlight the role of dietary salt, immunity and genetic predisposition in hypertensive heart disease pathogenesis.